Financiamento de campanhas eleitorais e corrupção - Costa, Thais Cristina Alves da (2020)
The Brazilian electoral system has its history determined by frauds, lies and crimes, a picture that is worsen by the inadequate functioning of its Electoral Justice System. Plenty electoral reforms were implemented; however, the approved normative texts are far from representing an electoral legal ruling that aims to tutor the Brazilian political order. During the past years, special publicity was given to the electoral corruption emerged from the “public-private partnership”, which not only did result in construction overbilling, embezzlement of public funds and the defence of private interests to the detriment of social interests, but has also changed the electoral system in a way that the corruption issue, in this field, started to be seen not as structural, but as an inherent practice to the private system of financing political campaigns. Given this political movement, in which numerous reforms are developed, they are still not enough to correct the structural and normative deficiencies, thoroughly relevant to the prevention of this practice. Therefore, this thesis has as its scope to identify which are the most common ways through which corruption is inserted in the context of financing political campaigns, pointing out what are the normative weaknesses originated in the collection and accountability systems through the analysis of the electoral accountability system in order to present, in the end, which preventive actions can be adopted by the State as to fight corruption